Seasonal Variations in Environmental Parameters of Kao Bay, North Halmahera, North Maluku Province, Indonesia - Inayah Inayah; Juharni Juharni (Program Studi Manajemen Sumber Daya Perairan, Fakultas Perikanan dan Ilmu Kelautan, Universitas Khairun, 2026)
Seasonal changes can alter the physical and chemical properties of seawater. This study aimed to investigate the seasonal variations in water temperature, salinity, water pH, sediment pH, dissolved oxygen, redox potential, total organic matter (TOM), and sediment texture during two contrasting seasons, namely the west monsoon (rainy season) and the east monsoon (dry season), in order to assess the level of metal contamination in the waters of Kao Bay, North Maluku Province, Indonesia. The study was conducted by collecting water quality and sediment samples from Kao Bay, particularly in the waters surrounding the NHM gold mining area. Water temperature, salinity, water pH, sediment pH, dissolved oxygen, and redox potential were measured in situ, while total organic matter was analyzed following the APHA, AWWA, and WEF (2005) standard methods (Part 5000: Aggregate Organic Constituents). Sediment texture was determined using the pipette method and expressed as percentage composition according to the Wentworth scale. The results showed significant seasonal variations in water temperature, salinity, water pH, sediment pH, total organic matter, redox potential (Eh), and sediment texture, which in turn influenced the distribution and concentration of metals in the study area.